2019
DOI: 10.1111/apt.15521
|View full text |Cite|
|
Sign up to set email alerts
|

Long‐term clinical outcomes in patients with chronic hepatitis delta: the role of persistent viraemia

Abstract: Summary Background Chronic hepatitis delta is a severe liver disease with rapid progression to cirrhosis. The impact of hepatitis delta virus (HDV)‐RNA on disease progression and interferon treatment in a real‐world cohort has been barely explored. Aim To assess the development of clinical events in a cohort of chronic hepatitis delta patients according to the presence or absence of HDV‐RNA Methods Multicentre study at four academic hospitals in Spain included anti‐HDV‐positive patients with compensated liver … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
59
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 59 publications
(66 citation statements)
references
References 30 publications
5
59
1
1
Order By: Relevance
“…Alone, HDV is unable to produce infectious viral particles, as it requires the envelope protein from its helper virus, Hepatitis B (HBV) [19]. HDV infection aggravates liver cirrhosis caused by HBV and worsens clinical outcomes [20].…”
Section: Expanding the Boundaries Of Known Viral Biodiversitymentioning
confidence: 99%
“…Alone, HDV is unable to produce infectious viral particles, as it requires the envelope protein from its helper virus, Hepatitis B (HBV) [19]. HDV infection aggravates liver cirrhosis caused by HBV and worsens clinical outcomes [20].…”
Section: Expanding the Boundaries Of Known Viral Biodiversitymentioning
confidence: 99%
“…In our cohort, 30% of subjects presented signs of cirrhosis already at baseline, and 27% progressed to cirrhosis within follow‐up. Several studies including ours have shown that the presence of hepatitis delta viremia is the main factor associated with development of clinical events …”
mentioning
confidence: 76%
“…The authors' declarations of personal and financial interests are unchanged from those in the original article …”
Section: Acknowledgementmentioning
confidence: 99%
See 1 more Smart Citation
“…Palom et al recently reported the results of a long‐term follow‐up study of patients with chronic hepatitis delta (HDV) enrolled from four academic hospitals in Spain . Their findings illustrate some of the major challenges we face in the management of this deadly disease.…”
mentioning
confidence: 99%